2008
DOI: 10.1159/000129614
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Immune Responses to Complex and Single Mycobacterial Antigens in Tuberculosis Patients with Diabetes

Abstract: Objective: To evaluate cell-mediated immune (CMI) response in diabetic and non-diabetic tuberculosis (TB) patients and healthy subjects in response to complex, fractionated and single antigens of Mycobacteriumtuberculosis. Material and Methods: Peripheral blood mononuclear cells (PBMC) were obtained from patients suffering from pulmonary TB and type II diabetes (n = 7), pulmonary TB without diabetes (n = 10) and healthy subjects without TB and diabetes (n = 10). PBMC were assessed for CMI responses in antigen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
(33 reference statements)
2
17
0
Order By: Relevance
“…The overall results suggest that infection with M. tuberculosis did not affect the level of Th1 cell reactivity to BCG and most antigens of M. tuberculosis used in this study. Furthermore, the study confirms strong to moderate (10,50). Although the gene for PPE68 is present in the M. tuberculosis-specific RD1 segment (13,36), statistically similar responses in the ESAT-6/CFP10 responders and nonresponders could be due to the presence of an immunodominant epitope (aa 124 to 137), which is conserved in several PPE proteins of M. tuberculosis, BCG, and environmental mycobacteria (48,57).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The overall results suggest that infection with M. tuberculosis did not affect the level of Th1 cell reactivity to BCG and most antigens of M. tuberculosis used in this study. Furthermore, the study confirms strong to moderate (10,50). Although the gene for PPE68 is present in the M. tuberculosis-specific RD1 segment (13,36), statistically similar responses in the ESAT-6/CFP10 responders and nonresponders could be due to the presence of an immunodominant epitope (aa 124 to 137), which is conserved in several PPE proteins of M. tuberculosis, BCG, and environmental mycobacteria (48,57).…”
Section: Discussionsupporting
confidence: 54%
“…The complex mycobacterial antigens used in this study were irradiated whole-cell M. tuberculosis H37Ra and M. bovis BCG (29,50), M. tuberculosis culture filtrate (MT-CF) enriched for secreted antigens, and purified M. tuberculosis cell walls (MT-CW) (48). MT-CF and MT-CW were kindly provided by J. T. Belisle (Colorado State University, Fort Collins, CO).…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies performed in the past have shown that MPT64 is relevant to immune response in humans [2][3][4][5] , and immunization of experimental animals with preparations containing MPT64 provided protection against challenge with M. tuberculosis [6] . Although these studies encourage the use of MPT64 as a new candidate vaccine against TB, this protein requires further characterization for promiscuous recognition by the immune system of M. tuberculosis -infected healthy individuals who did not progress to active disease, most probably due to the development of protective immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that MPT64 is recognized by TB patients in immunological assays [7][8][9][10][11] . In addition, MPT64 has also been shown to protect against M. tuberculosis infection in mouse models of TB [12,13] .…”
Section: Introductionmentioning
confidence: 99%